TEACHER LEADERSHIP IN INCREASING THE EFFECTIVENESS OF SOCIOLOGY LEARNING - Widiansyah, Subhan; Hardiansyah, Muhammad Agus; Naim, Mohammad (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to determine the leadership spirit of sociology teachers who are members of the Sociology Subject Teacher Consultation (MGMP) in Banten Province. Previous research has shown that students' motivation and learning achievement are highly dependent on the leadership spirit of teachers and teachers have a major role in shaping students' personalities. This shows that the teacher's leadership spirit affects students' learning motivation, and this leadership spirit has an important role for students to learn, work on, and complete school assignments. This research uses descriptive qualitative research methods which are carried out to members of the Sociology MGMP of Banten Province. This research will be a reference for sociology teachers in order to grow the leadership spirit of sociology teachers. This study uses descriptive qualitative research by interviewing sociology teachers and conducting Focus Group Discussions (FGD) to formulate effective leadership training for these teachers. Researchers facilitate and analyze the needs of sociology teachers in realizing effective sociology learning.  Based on the results of the FGD and interviews, it was concluded that an effective teacher is a teacher who is able to adapt his leadership style to the situation and condition of the students. Teachers cannot only apply certain leadership patterns without paying attention to the needs of their students, effective teachers are adaptive teachers and can see situations and conditions when to be authoritarian and when to be democratic.